Mobilizing transdisciplinary sustainability science in place-based communities: Evaluating saliency, legitimacy, and credibility in northern Canada - Kiri Staples (Elsevier, 2021)
The field of transdisciplinary sustainability science offers limited guidance on what it means to mobilize knowledge outside of conventional policy and decision-making settings. Research within this field tends to emphasize knowledge mobilization for conventional environmental policy venues and decision-makers such as state and industry actors. Place-based communities often make critical management decisions to advance sustainability and inform policy, yet the evaluation of sustainability science in these contexts is underexamined. Using a case study, community-based research approach, we explored how social processes in place-based communities shaped interpretations of sustainability science by those involved in and/or affected by research. We used core criteria for knowledge mobilization—salience, legitimacy, and credibility, as established by Cash et al. (2003) — to guide our analysis of how research knowledge was evaluated. Our analysis highlighted that specific relationships, perspectives and worldviews, and historical contexts shaped how salience, legitimacy and credibility were interpreted. We affirm that for knowledge to be effectively mobilized, it must be salient, legitimate and credible, but find that the definitions of these terms are highly dependant on the social contexts in which the research takes place. These insights are critical to future transdisciplinary research aimed at addressing complex sustainability problems impacting place-based communities.